Black Experience in Two Worlds: Minority Marginalization in Al-Mugri’s Blak Taste, Black Smell and Zakes Mda’s The Zulus of New York - Al-Khamisi, Fatima Ali (Journal of Ecohumanism, 2025)
This study explores the Black experience through a comparative analysis of Al-Mugri’s marginalized Akhdam community in Yemen in his novel Black Taste, Black Smell and Zakes Mda’s Zulus performers in The Zulus of New York. Examining these groups across historical, emotional, and social contexts, the research aims to achieve a twofold objective. Firstly, it seeks to identify universal themes within the Black experience, highlighting shared struggles faced by black communities despite geographical and cultural differences. Secondly, the study recognizes the distinct challenges faced by each group within their specific societal contexts. Through this comparative approach, the research offers a nuanced understanding of the complexities of the black, acknowledging both the unifying threads of marginalization and the unique realities shaped by each group’s historical and social background. Contribution: This study intervenes in Black experience scholarship by examining the intricate marginalization faced by Black characters navigating dual cultural contexts.